Redescription of the early zoeal stages of the snapping shrimp Synalpheus fritzmuelleri Coutière, 1909 reared in laboratory conditions - Santos, Rafael Carvalho [UNESP]; Pescinelli, Régis Augusto; Sene, Matheus [UNESP]; Pantaleão, João Alberto Farinelli; Costa, Rogerio Caetano [UNESP] (Cambridge University Press (CUP), 2025)
The present study described and illustrated the larval morphology of the three first zoeal stages (zoea I-III) of Synalpheus fritzmuelleri and compared with the previous described larvae of this species. The results pointed out a variety of differences among the descriptions, most of them related to the type and number of setae and articulation of appendages. The first zoea demonstrates similarities shared with the zoea I within the genus besides the diagnostic described characteristics. Other incongruences were also found such as the lack of information about some structures, such as the maxillule in the zoea I, and the use of ambiguous terms do designate type of setae. Moreover, the more advanced the zoea, additional differences were found among the previous and the current descriptions. Due to that, the necessity to review and also add new descriptions for Synalpheus larvae proves imminent to establish a standardization in the morphological description that will strengthen the comparative relationship in the genus.
Keywords: Alpheidae; Caridea; larval development; larval morphology